The Doctrine of St John of Damascus on the Death and the Assumption of Mary into Heaven, and its Possible Influence in the Corresponding Medieval Iconographies - Salvador González, José María (Eikón / Imago, 2017)
This paper aims to highlight the influence that the doctrine of St John of Damascus (c.675-c.749) on the death, resurrection and assumption of the Virgin Mary could have exercised over the complementary medieval iconographies of the Dormition and the Assumption of Mary into heaven. The article has two essential sides. In the first one, through the analysis of three homilies of Damascene on the Dormition of Mary, we deal with the author’s conceptual position on death, burial and the assumption of the soul of the Virgin, as well as with her anticipated resurrection and her assumption in body and soul into heaven. In the second side, some medieval paintings of the Dormition and the Assumption of Mary into heaven are interpreted from the doctrinal perspective of St John Damascene, putting in direct correspondence the narrative elements contained in these paintings with the formulations of the Syrian theologian in his three homilies on the Dormition.